2014
DOI: 10.3109/10428194.2014.946027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and prognosis of patients with primary sinonasal tract diffuse large B-cell lymphoma treated with rituximab-cyclophosphamide, doxorubicin, vincristine and prednisone chemotherapy: a study by the Consortium for Improving Survival of Lymphoma

Abstract: We evaluated the clinical outcomes and relapse patterns of 80 patients with primary sinonasal tract diffuse large B-cell lymphoma (SN-DLBCL) treated with rituximab-cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) chemotherapy at 22 institutions. A total of 59 (73.8%) patients received R-CHOP chemotherapy alone, whereas 21 (26.3%) were treated with R-CHOP followed by involved field radiotherapy (IFRT). In 73 patients with Ann Arbor stage I-II disease, no significant difference was found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Administration of consolidative RT was not associated with better event-free or OS, and overall prognosis was excellent. Consistently, a Korean study showed only one CNS recurrence among 80 cases of in sinonasal DLBCL (with 30% rate of intrathecal prophylaxis), and no difference in survival with RT, confirming that in the rituximab era neither RT nor routine intrathecal therapy are necessary (Table 2) [69]. Little is known about specific molecular features of DLBCL of the head and neck, except that 80% are non-GCB, with frequent gain of 1q31 (containing RGS1 , 55%) and loss of 9p21.3 (containing CDKN2A , 64%) [70].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 54%
“…Administration of consolidative RT was not associated with better event-free or OS, and overall prognosis was excellent. Consistently, a Korean study showed only one CNS recurrence among 80 cases of in sinonasal DLBCL (with 30% rate of intrathecal prophylaxis), and no difference in survival with RT, confirming that in the rituximab era neither RT nor routine intrathecal therapy are necessary (Table 2) [69]. Little is known about specific molecular features of DLBCL of the head and neck, except that 80% are non-GCB, with frequent gain of 1q31 (containing RGS1 , 55%) and loss of 9p21.3 (containing CDKN2A , 64%) [70].…”
Section: Prognosis Of Extranodal Dlbcl Arising From Specific Anatomicmentioning
confidence: 54%
“…Sinonasal lymphomas are relatively rare tumours of the head and neck. In this location, the most predominant lymphoma subtypes are DLBCL (seen more frequently in Western countries) and extranodal natural killer (NK)/T‐cell lymphoma, nasal type (more frequent in Asia) . The DLBCL of the sinonasal tract is an uncommon topographical variant.…”
Section: Introductionmentioning
confidence: 99%
“…The association of other extranodal sites with CNS 26 Based on all the above evidence, a new prognostic model to assess the risk of CNS disease in DLBCL (CNS-IPI) has been proposed. 27 This model has been validated in other series from the British Columbia Cancer Agency, 28 and includes the 5 IPI factors in addition to kidney/adrenal gland involvement, and it stratifies patients into 3 risk groups for CNS relapse: low risk (0-1 factors; 2-year risk of 0.6%), intermediate risk (2-3 factors; 2-year risk of 3.4%), and high risk (4-6 factors; 2-year risk of 10.2%).…”
Section: Guidelines For Diagnosis Prevention and Management Of Centrmentioning
confidence: 99%